ISLAM DAN DEMOKRASI (Telaah lmplementasi Demokrasi di Negara Muslim) - Zainuddin, M. (ULUL ALBAB Jurnal Studi Islam, 2002)
This paper is intended to analyze the element of democracy in Islam perspective and how Islamic government applies these concepts. This study is also aimed at proving Huntington and Fukuyama’s thesis stating that, in Reality, Islamic society does not practice the democracy principles. Seen from its norms, Islam teachings own democracy principles and elements, which are globally stated. These are known as: as-Syura, Al-Adalah, al-amanah, al-masuliyyah and al-hurriyah. These principles were perfectly applied in the prophet Muhammad lifetime and four Chalifah eras. Howerer, most Moslem countries do not practice these principles and neither do western countries.